The islanders - Monroe, Mary Alice; May, Angela (Angela M.) (New York : Aladdin, 2021)
Spending the summer with his grandmother on South Carolina's Dewees Island, eleven-year-old Jake finds two friends who are also struggling with family issues and together they try to save a sea turtle nest from predators.
Includes bibliographical references.
Ages 8 to 12.
Keywords: Friendship -- Juvenile fiction; Sea turtles -- Juvenile fiction; Turtles -- Juvenile fiction; Wildlife conservation -- Juvenile fiction; Dewees Island (S.C.) -- Juvenile fiction